Preparation of Bicyclic Ketal Skeletons with Aldehyde and α-Ketone Acid through Cascade Friedel–Crafts Reaction and Stereoselective Acetalization in One Pot - Li, Ling; Wang, Ying-wei; Zhang, Shi-qi; Deng, Xiong-fei; Li, Guang-xun; Zhao, Gang; Tang, Zhuo (Synlett, 2019)
Bicyclic ketal skeletons are important structure fragments that are frequently contained in natural products. A novel tandem Friedel–Crafts reaction and subsequent stereoselective acetalization were developed with readily available aldehyde and ketone acid. The reaction proceeded smoothly in the presence of catalytic Brønsted acid and afforded the corresponding product with moderate yield and high stereoselectivity.
Keywords: bicyclic ketal skeletons; Friedel–Crafts reaction; tandem reaction; α-ketone acid; Brønsted acid; acetalization